Management of Hypertension in the Elderly in Jember with the approval of the Self Transcendence Theory - Sofia Rhosma Dewi (Poltekkes Kemenkes Kupang, 2018)
Background: Hypertension is one of chronic disease in elderly. Conventional treatment of hypertension using drugs are not always show positive outcome. Nurse as a health practitioner need to find out another aspect to enhance elderly health status. One of them is through holistic care with spiritual care as their core. This research is conduct to find out the effect of transcendence spiritual care to the health status of elderly with hypertension. Methode: It’s a quasy experimental research with 46 respondents taken by simple random sampling. The data was taken by using SF 12 questionnaire to find out health perception and by measuring respondent’s blood pressure at the beginning and at the end of research. Result and Analysis: The result show that there is significant difference between health perception among experimental group before and after treatment (p = 0,000 for physical and mental health). There is no significant difference between health perception among control group before and after treatment (p = 0,347 for physical health and p = 0,295 for mental health). There is significant difference among health perception among expertimental and control group after treatment (p = 0,000 for physical health and p = 0,004 for mental health). Blood pressure measurement show significant difference for sistolic blood pressure (p = 0,000) but not for diastolic blood pressure p = 0, 157) among experimental group before and after treatment. In control group, sistolic and diastolic blood pressure show no significant difference (p = 0,153 for sistolic blood pressure p = 0,317 for diastolic blood pressure).